Cylindrical Vector Beams with an MOPA Amplifier Based on Nonlinear Polarization Rotation Mode-Locking - Tianyu Zhang; Dong Li; Siqi Pei; Yun Zhu; Jiapeng Hu; Xuesheng Liu; Anru Yan; Youqiang Liu; Zhiyong Wang (Photonics)
CVBs (cylindrical vector beams) are widely used in optical imaging, optical trapping, material processing, etc. In this study, based on mode-selective couplers and passive mode-locking fiber technology, a cylindrical vector fiber amplifier with an MOPA (master oscillator power amplifier) structure was developed. In the experiment, the pre-amp stage reached 19.87 mW output power and a CVB output with a mode purity greater than 97%. The measured beam quality factor was M2 = 2.1. The CVB output power obtained by the first-amp stage was 152.4 mW, and the mode purity was greater than 92%. The measured beam quality factor was M2 = 1.99. The internal inhomogeneity and external effects of the isotropic LMA (large-mode-area) fiber led to a decrease in beam quality and mode purity. After amplification, the gain of the fundamental mode was higher and the power was greater, resulting in a greatly reduced mode purity. This CVB fiber amplifier yielded important research value in expanding the applications of high-power fiber lasers.